Análise da aplicação do Selo Casa Azul em empreendimentos habitacionais verticais em Caxias do Sul, RS - Fastofski, Daniela Chiarello (Universidade do Vale do Rio dos Sinos, 2014)
The construction industry has great importance to the global economy, while it is characterized as an activity that generates significant environmental and social impacts. Incorporating strategies that provide more sustainable buildings is essential so that one can help to minimize these impacts and greater quality of life to the communities involved. Environmental certifications indicates guidelines that can guarantee the achievement of a more sustainable development. The Selo Casa Azul (Blue House Seal), awarded by the Brazilian federal bank Caixa, it’s a classification system developed for the brazilian reality considering regional aspects. This study was oriented to verify the feasibility of applying this certification. The specific objectives are analyze vertical housing developments as its suitability for the Selo Casa Azul, identify existing limitations to meet the requirements and their correlation to different construction standards and which of these could become more easily met from simple changes. The research is based on case studies in typical housing developments in Caxias do Sul, Brazil subsidized by different resources. As a result, it was found that the Selo Casa Azul demonstrates the relative ease of application, therefore, a viable tool, although necessary clarifications from bank’ staff. Concerning the construction standards some criteria may be more easily seized when the resources are not limited, however, it was observed that part of difficulty of fitness is due to the practices of companies and the construction itself. From the results it was also verified that none of the analyzed developments attend the Seal, since all fail to satisfy a mandatory criterion, and none has reached at least 50 % of total proposed criteria. Of the 53 criteria, about 25 % were not attended by all of the developments.
Keywords: Habitação; Selo Casa Azul; Construção sustentável; Housing; Sustainable buildings; ACCNPQ::Engenharias::Engenharia Civil